Winning the peace : America and world order in the new era - Ruggie, John Gerard (New York : Columbia University Press, 1996)
"A Twentieth Century Fund book."
Keywords: United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- 1989-.; World politics -- 1989-.